2019
DOI: 10.2478/intox-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

Positive and inverse correlation of blood lead level with erythrocyte acetylcholinesterase and intelligence quotient in children: implications for neurotoxicity

Abstract: Blood lead level (BLL) is insufficiently sensitive for early detection of Lead-induced neurotoxicity (LIN). This study determined the possible role of the combination of BLL, intelligent quotient (IQ) and erythrocyte acetylcholinesterase (AChE) activity in the early detection of LIN in Children. Apparently healthy children (n=309) from eight public primary schools in Ibadan, Nigeria were recruited and classified into: children with Elevated BLL (EBLL) and children with Acceptable BLL (control) based on CDC cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…At concentrations above 10 μg/dL, the IQ score was much lower than at concentrations below 10 μg/dL [ 27 ]. In another study performed at a concentration of 10 μg/dL compared to 5 μg/dL, the IQ score in the case group (85.9 11 ± 11.6) and in the control group (91.5 ±14.0) showed a higher IQ score for lower concentrations [ 28 ]. In another study based on the Beery VMI Saudi-based standard scores test, it was found that at concentrations below 10 μg/dL, the IQ score was 101.39 ± 14.18, while at concentrations above 20 μg/dL, the IQ score decreased to 85.14 ± 12.94 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…At concentrations above 10 μg/dL, the IQ score was much lower than at concentrations below 10 μg/dL [ 27 ]. In another study performed at a concentration of 10 μg/dL compared to 5 μg/dL, the IQ score in the case group (85.9 11 ± 11.6) and in the control group (91.5 ±14.0) showed a higher IQ score for lower concentrations [ 28 ]. In another study based on the Beery VMI Saudi-based standard scores test, it was found that at concentrations below 10 μg/dL, the IQ score was 101.39 ± 14.18, while at concentrations above 20 μg/dL, the IQ score decreased to 85.14 ± 12.94 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This correlates with a supralinear association between lead concentrations and neurobehavioral prognosis. Another finding indicated that blood lead level is inchoately sensitive to recognise or detect lead-induced toxicity early [22]; and suggests erythrocyte AChE as a marker for early detection of veritable environmental lead exposure and lead-induced neurotoxicity in children. Universal cognitive potential or general intelligence comprises diverse correlated attributes.…”
Section: Neurotoxicity and Neurobehavioral Deficitsmentioning
confidence: 99%